Representasi Konflik Aceh dalam Cerpen Kontemporer Pascaperjanjian Damai - Qalbi, Syifa Ul; Mulyati, Yeti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to examine the representation of the Aceh conflict in Raisa Kamila’s short stories Mati Lampu and Cerita dari Cot Panglima, published in 2020. The research used a qualitative descriptive method, with data collection carried out though library research and note-taking techniques. A sociological approach to literature was employed, alongside the application of Hall’s concept of representation. The results show that Mati Lampu represents the Aceh conflict as daily events filled with threats and alarms. In contrast, Cerita dari Cot Panglima, portrays the conflict as depriving civilians of security and fostering sentiments against the Javanese ethnicity.